Short-term impacts of energy wood harvesting on ectomycorrhizal fungal communities of Norway spruce saplings - Huusko, Karoliina (ISME J, 2015)
The increased demand for harvesting energy wood raises questions about its effects on the functioning of the forest ecosystems, soil processes and biodiversity. Impacts of tree stump removal on ectomycorrhizal fungal (EMF) communities of Norway spruce saplings were studied with 454-pyrosequencing in a 3-year field experiment replicated in 3 geographical areas. This is possibly the most thorough investigation of EMF communities associated with saplings grown on sites subjected to energy wood harvesting. To separate impacts of tree stump and logging residue removal on EMF and plant variables, we used three harvesting treatments with increasing complexity from patch mounding alone (P) to patch mounding combined with logging residue removal (RP), and patch mounding combined with both logging residue and stump removal (SRP). Saplings grown in uncut forests (F) served as references for harvesting treatments. A majority of sequences (>92%) and operational taxonomic units (OTUs, 55%) were assigned as EMF. EMF OTU richness, fungal community composition or sapling growth did not differ between harvesting treatments (P, RP and SRP), while EMF OTU richness, diversity and evenness were highest and sapling growth lowest in the undisturbed reference forests (F). The short study period may partially explain the similarities in fungal and sapling variables in different harvesting treatments. In conclusion, our results indicate that neither stump removal nor logging residue removal have significant additional negative impacts on EMF communities or growth of Norway spruce saplings in the short-term compared with the impacts of more conventional harvesting methods, including clear cutting and patch mounding.